Procurement and Operation Technical For Meniran (Phyllanthus Niruri) Extraction Equipment - Budi Santoso; Fitrian Imaduddin; Heru Sukanto; Joko Triyono; Raymundus Lulus Lambang Govinda Hidayat; Purwadi Joko Widodo; Dwi Heru Siswantoro (Mekanika: Majalah Ilmiah Mekanika, 2021)
At this time the government prohibits the use of antibiotics in animal feed as an Antibiotic and Growth Promoter (AGP), so an effective and safe immunomodulator and herbal growth stimulant product are needed through Meniran extract products (Phyllanthus niruri) and chemicals in the market are not yet optimal as immunomodulators and growth stimulants. CV. Maxipro Agrosatwa which is engaged in veterinary medicine, wholesale trade of agricultural products, and other live animals will produce feed using Meniran extract products. Extraction equipment that is needed is a Rotary vacuum evaporator. This equipment is needed to separate the solvent from the solute without high heating which will damage the solute content. The vacuum condition in the flask is to make the separation more efficient as well as accelerate the separation of the solvent from a solution by reducing the boiling point. The rotation of the flask is to increase evaporation. The complexity of this equipment is what makes CV. Maxipro Agrosatwa cannot handle it alone and requires technical assistance from the Department of Mechanical Engineering (Jurusan Teknik Mesin-JTM) FT UNS. Technical assistance provided by JTM FT UNS is in the form of procurement, delivery, installation, operation, and maintenance of the rotary vacuum evaporator.